Serum IL‐17A concentration and a IL17RA single nucleotide polymorphism contribute to the risk of autoimmune type 1 diabetes. Issue 6 (25th May 2022) - Li, Junxian; Xu, Lei; Zhao, Weijing; Pan, Jiemin; Lu, Junxi; Lu, Huijuan; Yan, Jinhua; Weng, Jianping; Liu, Fang
Abstract: Aims: Interleukin (IL)‐17 is associated with autoimmunity. This study aimed to affirm the role of IL‐17A, IL‐17F and single nucleotide polymorphisms (SNPs) in genes related to them and their receptors in autoimmune type 1 diabetes (T1D) for Chinese population. Methods: In this study, 130 patients with autoimmune T1D and 140 non‐T1D controls were included for analysis. Clinical and biochemical data were collected, and serum levels of IL‐17A, IL‐17F, IL‐6, and high‐sensitivity C reactive protein were measured using ELISA. The SNPs rs2275913, rs8193036, rs3819025, rs763780, rs879577, rs4819554, and rs708567 were genotyped using the SNaPshot assay. Results: IL‐17A levels were higher in patients with autoimmune T1D than in controls (median [IQR] 28.83[37.38] vs. 16.68[8.10], p  < 0.001) and high IL‐17A was a risk factor for autoimmune T1D (odds ratio (OR), 1.013; 95% CI, 1.003–1.023; p  = 0.013) after adjusting for confounding factors. Linear regression analysis revealed that log10 IL‐17A levels were independently associated with fasting C‐peptide, IL‐6, body mass index, and IL‐17F. However, no independent association was found between IL‐17F and autoimmune T1D. The GG genotype of SNP rs4819554 in the interleukin 17 receptor A ( IL17RA ) gene was associated with a decreased risk of autoimmune T1D (OR, 0.458; 95% CI, 0.246–0.852; p  = 0.014) after adjusting for other confounders. The IL17RA rs4819554 GG genotype was negatively correlated with serum glutamic acid decarboxylase antibody appearance ( p  < 0.05). Conclusions: Increased serum IL‐17A, but not IL‐17F, is a risk factor for autoimmune T1D. The GG genotype of IL17RA rs4819554 might decrease the risk for autoimmune T1D.